Economic efficiency and growth: Evidence from Brazil, China and India - Nader Nazmi; Julio E. Revilla (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
We compare economic efficiencies in Brazil, India, and China, where economic efficiency measures the gap between potential and actual output for a given input combination and technological factor. We use stochastic production frontier models to measure the contributions of factors of production and technology to growth and estimate non-positive error terms that capture production inefficiencies in each country. The results suggest that China and India had relatively inefficient production in the early 1980s but have since improved production efficiency substantially. In the same period, production efficiency in Brazil has declined somewhat from relatively high initial levels and the gap between production efficiency between these countries has narrowed substantially, supporting more rapid growth in China and India relative to Brazil.
Keywords: F43; O24; 330; growth; trade; production; Wirtschaftswachstum; Gesamtwirtschaftliche Produktion; Wirtschaftspotenzial; Brasilien; Indien; China